O estudo de aula para a implementação da alfabetização científica nos anos iniciais - Gonçalves, Simone Munafó Tostes (2022)
This work addresses aspects of teacher training through a collaborative process that is configured from the Classroom Study approach. The study took place during the COVID-19 pandemic with 13 elementary school teachers from a public school in the city of Sorocaba/SP, in a formative process for the teaching of science of interest in the implementation of scientific literacy. Taking into account that the Classroom Study takes place in stages of development, the teachers went through a conceptualization with the theme chosen in their theoretical approach, collaboratively carried out lesson plans, applied and investigated the proposals of the contents and, finally, carried out analyzes reflective. This process proved to be effective for the development of the introductory implementation of scientific literacy where the teachers developed aspects of the collaborative culture among their peers, favoring their professional development.